Template-Independent Repair of the 3′ End of Cucumber Mosaic Virus Satellite RNA Controlled by RNAs 1 and 2 of Helper Virus - Burgyán, József (American Society for Microbiology, 1998)
RNA viruses which do not have a poly(A) tail or a tRNA-like structure for the protection of their vulnerable 3′ termini may have developed a different strategy to maintain their genome integrity. We provide evidence that deletions of up to 7 nucleotides from the 3′ terminus of cucumber mosaic cucumovirus (CMV) satellite RNA (satRNA) were repaired in planta in the presence of the helper virus (HV) CMV. Sequence comparison of 3′-end-repaired satRNA progenies, and of satRNA and HV RNA, suggested that the repair was not dependent on a viral template. The 3′ end of CMV satRNA lacking the last three cytosines was not repaired in planta in the presence of tomato aspermy cucumovirus (TAV), although TAV is an efficient helper for the replication of CMV satRNA. With use of pseudorecombinants constructed by the interchange of RNAs 1 and 2 of TAV and CMV, evidence was provided that the 3′-end repair was controlled by RNAs 1 and 2 of CMV, which encode subunits of the viral RNA replicase. These results, and the observation of short repeated sequences close to the 3′ terminus of repaired molecules, suggest that the HV replicase maintains the integrity of the satRNA genome, playing a role analogous to that of cellular telomerases.